Assistência pré-natal e persistência da sífilis congênita - Brito, Antonia Aila Coelho Barbosa (2016)
Syphilis is a systemic infectious and sexually transmitted disease caused by the bacterium Treponema Pallidum, which can also be transmitted from mother to child during pregnancy. It is estimated that 1.8 million pregnant women worldwide are infected with syphilis and less than 10% are diagnosed and treated correctly. Prenatal care represents a very relevant moment to identify this condition and, consequently, the treatment of the woman and the partner. The objective of this study was to analyze prenatal care of pregnant women with syphilis, identifying factors of institutional vulnerability that contributed to the birth of children with congenital syphilis. It was a cross-sectional study with a descriptive approach in a Regional Health Department of the city of Fortaleza. One hundred mothers whose live children were notified with syphilis and reported to the SINAN bank were included in this study. The Chi-square test was performed using a statistical significance level of 5% (p <0.05). The results indicate the mean age of 26.6 years, single (57.0%), low schooling (39.0%), household (74.0%). Among the single women (p = 0.007), the majority did not perform prenatal care (88.6% vs. 50.6%). Of those who underwent prenatal care, 66% started in the first trimester and 60% with six or more visits. 55.0% were diagnosed with syphilis during prenatal care, 58.0% did not start treatment and 45% of the partners were not tested. Regarding vulnerabilities, 93.0% are low-income, 40.0% are alcohol and crack users, and 19.0% are domestic violence victims. There were statistically significant differences (p <0.001) between the mothers who did and those who did not prenatal in the amount of three or more vulnerabilities. Finally, in order to reduce the rates of congenital syphilis, it is necessary to have 100% adherence to prenatal care in the first trimester and to perform six or more visits, The conditions of vulnerabilities and risks to which they are exposed.